2020
DOI: 10.5114/ada.2019.83501
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in patients with systemic sclerosis

Abstract: Introduction Patients with systemic sclerosis experience endothelial dysfunction and damage even in the absence of clinical manifestations. Aim To evaluate various methods for assessing the endothelial function for their applicability to clinical practice. Material and methods Forty-two patients (7 men and 35 women) with systemic sclerosis and 36 controls (11 men and 25 women) matched for age, sex, body mass index, smoking habit, and comorbid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…Although, pathogenesis of SSc is still not fully understood, the emerging data, particularly those on animal models and using molecular biology, demonstrates overexpression of the genes related to the tissue remodelling and fibrosis, such as transforming growth factor β and platelet-derived growth factor in the sclerotic skin (5). Moreover, it has been documented that SSc is related to the endothelial injury, characterised by impaired arterial flow-mediated dilatation and release of numerous procoagulant molecules, including tissue factor (TF) and von Willebrand factor into the circulating blood (6,7). Currently, rising number of reports have indicated that cellular fibronectin (cFN) in peripheral blood might be a novel and specific biomarker of endothelial damage (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Although, pathogenesis of SSc is still not fully understood, the emerging data, particularly those on animal models and using molecular biology, demonstrates overexpression of the genes related to the tissue remodelling and fibrosis, such as transforming growth factor β and platelet-derived growth factor in the sclerotic skin (5). Moreover, it has been documented that SSc is related to the endothelial injury, characterised by impaired arterial flow-mediated dilatation and release of numerous procoagulant molecules, including tissue factor (TF) and von Willebrand factor into the circulating blood (6,7). Currently, rising number of reports have indicated that cellular fibronectin (cFN) in peripheral blood might be a novel and specific biomarker of endothelial damage (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Vascular injury is an early event in the pathogenesis of SSc that appears before the development of fibrosis and immune abnormalities [ 16 ]. In this study, we assessed vascular fibrosis in the lung tissue of the SSc mouse model using masson staining, and found that the pulmonary vessels of the mice in the BLM group exhibited significant fibrosis and reduction in thediameter of the vessels compared with the PBS group (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During the occurrence and development of SSc, the activation of endothelial cells is the main manifestation of vascular endothelial cell dysfunction, which is mainly characterized by increased expression of adhesion molecules on the surface of endothelial cells [ 16 ]. Cell adhesion molecules such as vWF, ICAM-1, VCAM-1 and SELE located on the surface of vascular endothelial cells are necessary for the adhesion of platelets and leukocytes [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Systemic autoimmunity and environmental triggers are the possible pioneers of vasculopathy, which is characterized by both abnormal activation and damaged endothelial cells [21]. Brachial arterial FMD measurement is a surrogate marker of endothelial function and a signi cant reduction in the FMD in SSc patients has been documented in the literature [9,[22][23][24].There is a paucity of data regarding the effect of treatment on ED of SSc and the correlation among the markers of ED, vasoactive, angiogenic, and brogenic mediators. We strati ed our SSc patients based on the therapeutic regimen and found asigni cant reduction in the FMD across all patient groups.…”
Section: Discussionmentioning
confidence: 99%